Production Process Time Reduction Strategy through SMED Method Implementation - Andi Dwi Wahyu Wibowo; Taufik Rachmad Fauzy; Surjo Hadi (Jurnal Teknologi dan Manajemen, 2026)
The increasingly competitive manufacturing industry demands companies to improve operational efficiency, particularly in the changeover process, which contributes to production downtime. This study aims to analyze the application of the Single Minute Exchange of Dies (SMED) method in reducing setup time in the packaging process to improve production efficiency. The study uses a quantitative approach through direct observation, measuring work time, identifying internal and external setup activities, converting internal activities to external ones, and simplifying non-value-added activities. The results show that the application of SMED can reduce setup time from 265 minutes to 180 minutes, a reduction of 85 minutes (32%). Improvements were made through optimizing the mold installation process, which saved 20 minutes, improving eyemark settings, which reduced the time by 5 minutes, and improving cutter settings, which reduced the duration from 120 minutes to 60 minutes. The research findings prove that the SMED method is effective in increasing the efficiency of the changeover process, reducing production downtime, and increasing productivity in the packaging process. This study provides a practical contribution as a reference for the application of SMED in an effort to improve operational performance in manufacturing industries with similar product changeover characteristics.